2007
DOI: 10.1590/s0102-05362007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de alface e rabanete em cultivo consorciado estabelecido em diferentes épocas e espaçamentos entre linhas

Abstract: O trabalho foi conduzido na UNESP, Jaboticabal-SP, de maio a agosto de 2001, com objetivo de avaliar a produtividade de alface e rabanete em função do espaçamento e da época de estabelecimento do consórcio. Os 14 tratamentos foram avaliados em blocos ao acaso, com quatro repetições e parcelas de 20 plantas, sendo resultado da combinação dos fatores espaçamento entre linhas da alface (0,3 e 0,4 m), sistemas de cultivo (consórcio e monocultivo) e época de semeadura do rabanete (0; 7 e 14 dias após o transplantio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Also B i e s i a d a [5] found that a higher plant density had a significant favorable effect on the yield of kohlrabi, but decreased the mean bulb mass. F i l h o et al [33] found that decreasing the distance between rows from 40 to 30 cm caused a decrease in the mean mass of lettuce heads from 406.3 to 321.1 g. Furthermore, other studies confirmed that decreasing the area per plant contributed to a higher yield but to a lower mass and diameter of the edible part of plants [3][4][34][35][36][37][38]. This might be due to a less light reaching the plants [20,39].…”
Section: Discussionmentioning
confidence: 99%
“…Also B i e s i a d a [5] found that a higher plant density had a significant favorable effect on the yield of kohlrabi, but decreased the mean bulb mass. F i l h o et al [33] found that decreasing the distance between rows from 40 to 30 cm caused a decrease in the mean mass of lettuce heads from 406.3 to 321.1 g. Furthermore, other studies confirmed that decreasing the area per plant contributed to a higher yield but to a lower mass and diameter of the edible part of plants [3][4][34][35][36][37][38]. This might be due to a less light reaching the plants [20,39].…”
Section: Discussionmentioning
confidence: 99%
“…According to Cecílio Filho et al (2007), with LER values greater than 1, intercropping will favor the growth of the companion crops. This indicates that this cropping system more efficiently uses environmental resources.…”
Section: Agronomic Advantage Indicesmentioning
confidence: 99%
“…Trabalhos realizados por outros autores, em ambientes diversos, com outras variedades, com arranjos e formas de cultivo diferentes, apontam um efeito positivo do consórcio rabanente-alface sobre a produção de alimentos por unidade de área (CECÍLIO FILHO e MAY, 2002;REZENDE et al, 2003;OLIVEIRA et al, 2004;REZENDE et al, 2005;CECÍLIO FILHO et al, 2007;GRACIANO et al, 2007;TAVELLA et al, 2011;SUGASTI et al, 2013). Portanto, o presente trabalho corrobora com os dados existentes na literatura.…”
Section: Resultsunclassified
“…Além disso, a consorciação contribui para a estabilidade da atividade rural, assegurando colheitas escalonadas e possibilitando renda adicional para o produtor. Deste modo, no cenário atual, em que se busca uma agricultura de menor impacto ambiental, o cultivo consorciado, ao otimizar o uso dos insumos, contribui para que olericultura, altamente demandante de recursos naturais e insumos agrícolas, seja praticada de forma mais sustentável (CECÍLIO FILHO et al, 2007).…”
Section: Introductionunclassified